Localization of Hidden Attractors in Chua’s System With Absolute Nonlinearity and Its FPGA Implementation - Wu, Xianming; Wang, Huihai; He , Shaobo (Frontiers in Physics, 2021)
Investigation of the classical self-excited and hidden attractors in the modified Chua's circuit is a hot and interesting topic. In this paper, a novel Chua's circuit system with an absolute item is investigated. According to the mathematical model, dynamical characteristics are analyzed, including symmetry, equilibrium stability analysis, Hopf bifurcation analysis, Lyapunov exponents, bifurcation diagram and the basin of attraction. The hidden attractors are located theoretically. Then the coexistence of the hidden limit cycle and self-excited chaotic attractors are observed numerically and experimentally. The numerical simulation results are consistent with the FPGA implementation results. It shows the hidden attractor can be localized in the digital circuit.